Matrics and vector spaces - Blyth, T S; Robertson, E F (Cambridge Cambridge university press, 1984)
Matrices and vector spaces are fundamental concepts in linear algebra. A vector space is a set of objects (vectors) that can be added together and multiplied by scalars, satisfying certain axioms. Matrices, which are rectangular arrays of numbers, can be used to represent linear transformations and systems of linear equations within vector spaces.
Keywords: Mathematics